Sosialisasi dan Pengajaran Pendidikan Karakter pada Anak-Anak TPQ dengan Media Video Animasi - Kristin Marwinda; Novita Al Ihyak Dieni; Inti Englishtina; Steffie Mega Mahardhika (Jurnal Pengabdian Masyarakat (ABDIRA), 2022)
This community service is one of the activities in the community partnership program. The targets are people who are not economically productive, namely the students of the Qur'an Education Park/ TPQ Asy Syifa' Darussalam in Ringinarum District, Kendal Regency. The activity carried out in this community partnership program is to provide teaching about character education to children with video media. Animated videos were chosen as learning materials because children are usually more interested and easier to learn and understand something based on audio visuals. The study method on the results of this community service uses a qualitative descriptive study. The results of the activity showed that the children were quite enthusiastic in learning the material from the videos provided. The children looked more interactive in the discussion and question and answer (QA) sessions after the video screening and presentation of the material. They are also motivated to learn and practice moral values in their daily lives, so that the children not only  will be able to learn religious education, but they will also  have a good attitude and behavior.